Middle Eastern and North African societies in the interwar period - Boyar, Ebru; Fleet, Kate (Social, economic and political studies of the Middle East and Asia, 2018)
Taking society as its central focus, Middle Eastern and North African Societies in the Interwar Period approaches the region as one of connectivities and fluidity and investigates networks and interregional relations, stratagems adopted to shape society and social resistance to or absorption of change. From tourism to health propaganda, marriage to beauty contest, mass communication to music, this book offers a vibrant and dynamic picture of the region which goes beyond state borders --